Project ASPIRE: Spoken Language Intervention Curriculum for Parents of Low-socioeconomic Status and Their Deaf and Hard-of-Hearing Children. Issue 2 (February 2016) - Suskind, Dana L.; Graf, Eileen; Leffel, Kristin R.; Hernandez, Marc W.; Suskind, Elizabeth; Webber, Robert; Tannenbaum, Sally; Nevins, Mary Ellen
Abstract : Objective: To investigate the impact of a spoken language intervention curriculum aiming to improve the language environments caregivers of low socioeconomic status (SES) provide for their D/HH children with CI & HA to support children's spoken language development. Study Design: Quasiexperimental. Setting: Tertiary. Patients: Thirty-two caregiver–child dyads of low-SES (as defined by caregiver education ⩽ MA/MS and the income proxies = Medicaid or WIC/LINK) and children aged <4.5 years, hearing loss of ≥30 dB, between 500 and 4000 Hz, using at least one amplification device with adequate amplification (hearing aid, cochlear implant, osseo-integrated device). Intervention: Behavioral. Caregiver-directed educational intervention curriculum designed to improve D/HH children's early language environments. Main Outcome Measures: Changes in caregiver knowledge of child language development (questionnaire scores) and language behavior (word types, word tokens, utterances, mean length of utterance [MLU], LENA Adult Word Count (AWC), Conversational Turn Count (CTC)). Results: Significant increases in caregiver questionnaire scores as well as utterances, word types, word tokens, and MLU in the treatment but not the control group. No significant changes in LENA outcomes. Conclusion: Results partially support the notion that caregiver-directed language enrichment interventions can change home language environments of D/HH children from low-SES backgrounds. Further longitudinal studies are necessary.